2018
DOI: 10.3390/ijms19040939
|View full text |Cite
|
Sign up to set email alerts
|

Hinokitiol Inhibits Migration of A549 Lung Cancer Cells via Suppression of MMPs and Induction of Antioxidant Enzymes and Apoptosis

Abstract: Hinokitiol, a natural monoterpenoid from the heartwood of Calocedrus formosana, has been reported to have anticancer effects against various cancer cell lines. However, the detailed molecular mechanisms and the inhibiting roles of hinokitiol on adenocarcinoma A549 cells remain to be fully elucidated. Thus, the current study was designed to evaluate the effect of hinokitiol on the migration of human lung adenocarcinoma A549 cells in vitro. The data demonstrates that hinokitiol does not effectively inhibit the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
29
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 41 publications
3
29
0
1
Order By: Relevance
“…On the other hand, C. formosana leaf extracts also possessed cytotoxicity against bladder cancer cell growth (IC 50 value ≅ 10 μg/ml for TCCSUP, T24, and TSGH-8301 cells after treatment for 48 h) [16], suggesting that C. formosana leaf extracts may exhibit broadspectrum cytotoxicity against various cancer cells. As previously reported, some phytocompounds from C. formosana leaf extracts were able to inhibit cancer cell growth; for instance, hinokitiol inhibited A549 cell growth at a high dosage (more than 20 μM) [19]. Additionally, we found that yatein exerted a stronger inhibitory effect on the growth of the A549 cells (IC 50 value = 3.5 μM after treatment for 72 h) than did other lignans that have been reported to have anti-NSCLC growth effects in previous studies.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…On the other hand, C. formosana leaf extracts also possessed cytotoxicity against bladder cancer cell growth (IC 50 value ≅ 10 μg/ml for TCCSUP, T24, and TSGH-8301 cells after treatment for 48 h) [16], suggesting that C. formosana leaf extracts may exhibit broadspectrum cytotoxicity against various cancer cells. As previously reported, some phytocompounds from C. formosana leaf extracts were able to inhibit cancer cell growth; for instance, hinokitiol inhibited A549 cell growth at a high dosage (more than 20 μM) [19]. Additionally, we found that yatein exerted a stronger inhibitory effect on the growth of the A549 cells (IC 50 value = 3.5 μM after treatment for 72 h) than did other lignans that have been reported to have anti-NSCLC growth effects in previous studies.…”
Section: Discussionsupporting
confidence: 68%
“…Yuan et al [16] demonstrated that C. formosana leaf extracts induce G2/M cell cycle arrest and apoptosis in human bladder cancer cells. In addition, Jayakumar et al [19] reported that hinokitiol, a monoterpenoid isolated from C. formosana, inhibited the migration of A549 cells by suppressing the expression of matrix metalloproteinases. The finding implied that the C. formosana extract and its derived phytocompounds might be potential candidate therapeutic agents against lung cancer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this experiments, curcumin was used as a positive control to hinokitiol due to its well-established anticancer effects as a natural derived bioactive compound in the previous report [20]. Indeed, hinokitiol satisfactorily showed anti-cancer effects on cervical and lung cancer cells along the increased concentration and exposure time (Figure 1) in consistentwith earlier reports[12,13]. Interestingly, there have been the reports that autophagy is used for cell survival not only during nutrient deprivation condition of normal cells but also cancer cells as a self-protecting mechanism for sustaining tumor growth against toxicity of cancer therapy[21].…”
supporting
confidence: 86%
“…Recently, there has been a report that curcumin; hydrophobic polyphenol extracted from turmeric of the ginger family, directly interacts with TFEB for augmentation of TFEB nuclear translocation which ameliorates transcriptional activity of TFEB [10,11]. More recent findings suggest that hinokitiol affects cancer cells in various ways depending on the concentration; treatment with non-toxic dose (1∼5 M) of hinokitiol does not exert severe cytotoxicity to normal cells but suppression of migration ability of human lung adenocarcinoma cells [12]. Hinokitiol is also related to the suppression of cancer stemness and glioma oncogenicity by downregulation of Nrf2 expression; on the other hand, melanoma is notably inhibited by hinokitiol via increased activity of antioxidant enzymes catalase (AEC) and superoxide dismutase (SOD) as well as downregulation of proteolytic enzymes; matrix metalloproteinase (MMP-2 and -9) [13,14].…”
Section: Introductionmentioning
confidence: 99%